A influ??ncia do modelo de neg??cios no sucesso do projeto em organiza????es - Gon??alves, Marcelo Luiz do Amaral (2017)
In a wide range of activities, companies have been using the Business Model to represent the organization's strategy in delivering value and meeting the needs of its clients and segments with organizational efficiency and competitive differential. The business model presents itself as a very useful conceptual tool for capturing, sharing and creating a common view of the organization model. The projects are prominent in the strategic issues, because through them it is possible to materialize the planned strategic objectives and described in the Business Model of the company. The evaluation of project success can be accomplished by considering short and long-term objectives, uncertainties associated with the market, and technologies that may affect expectations about project success. This research analyzed the influence of the configuration of the business model in the project success in national and international companies from different fields of activity. In this study, each of the dimensions that constitute the Business Model was identified, as well as the dimensions of the Project Success. Additionally, was verified the contribution of the Business Model configuration in the overall configuration of the Business Model and the contribution of the Project Success dimensions in the overall success of the Project. This research is of an applied nature, characterized as confirmatory-descriptive and the data were obtained through a survey, using as a research instrument a structured questionnaire for data collection. The questionnaire was sent to a universe composed of professionals from various fields of activity, with leadership positions and who have already participated in projects, providing a number of 181 valid answers. The quantitative analysis was used to study the data collected in the research, using the Structural Equation Modeling (SEM) as the method and the Partial Least Square (PLS-SEM) as a technique for analyzing the data. The results showed that the configuration of the business model has a positive influence to the project success, explaining 46% of the effects on the success of projects developed in organizations of several branches of activities in several countries. As a contribution to professional practice, was proposed the Business Model??s Components Evaluation Model. This model aims to assess the maturity of each components that constitutes a Business Model, helping managers to diagnose which components need action to improve the maturity of Business Models in their organizations.